Cellular Receptors for Human Enterovirus Species A - Nishimura, Yorihiro; Shimizu, Hiroyuki (Frontiers in Microbiology, 2012)
Human enterovirus species A (HEV-A) is one of the four species of HEV in the genus Enterovirus in the family Picornaviridae. Among HEV-A, coxsackievirus A16 (CVA16) and enterovirus 71 (EV71) are the major causative agents of hand, foot, and mouth disease (HFMD). Some other types of HEV-A are commonly associated with herpangina. Although HFMD and herpangina due to HEV-A are common febrile diseases among infants and children, EV71 can cause various neurological diseases, such as aseptic meningitis and fatal encephalitis. Recently, two human transmembrane proteins, P-selectin glycoprotein ligand-1 (PSGL-1) and scavenger receptor class B, member 2 (SCARB2), were identified as functional receptors for EV71 and CVA16. In in vitro infection experiments using the prototype HEV-A strains, PSGL-1 and SCARB2 could be responsible for the specific receptors for EV71 and CVA16. However, the involvement of both receptors in the in vitro and in vivo infections of clinical isolates of HEV-A has not been clarified yet. To elucidate a diverse array of the clinical outcome of HEV-A-associated diseases, the identification and characterization of HEV-A receptors may provide useful information in understanding the HEV-A pathogenesis at a molecular level.